The Role of the Exchange Rate Stability in a Small and Open Economy: The Case of the Republic of Macedonia - Fatmir Besimi (National Bank of the Republic of Macedonia, 2004)
The purpose of this paper is to present the role of the exchange rate stability in a small and open economy, where the case of the Republic of Macedonia is investigated. Also, an accent is given to the role of the expectations of the economic agents for the future movements of the exchange rate, where the speculative implications might be very costly for the domestic economy because of the higher and more volatile interest rates under the regime of de facto fixed exchange rate. On the other side, the liberalization of the capital account raises the question of the flexibility of the exchange rate and the monetary policy autonomy, the socalled impossible trinity. But given the high level of currency substitution and emphasized pass-through effect of the exchange rate on prices, the exchange rate full flexibility is not recommended. The possible shift towards more flexible exchange rate should be very cautious, step-by-step and within narrow margins, having in mind the possible implications on the economy and the financial system. Also, the experiences of the countries in transition show that regardless of the monetary strategy they implement or the official exchange rate regime they have, the countries in transition simultaneously take care of the exchange rate stability.
Keywords: 330; Wechselkurspolitik; Balassa-Samuelson-Effekt; Kaufkraftparität; Exchange Rate Pass-Through; Währungssubstitution; Kleine offene Volkswirtschaft; Mazedonien